THE INFLUENCE OF COMPETENCE, SKILL AND EDUCATION OF FIELD AGRICULTURAL EXTENSION WORKERS ON THE QUALITY OF HUMAN RESOURCES OF FARMER GROUPS THE SUMURAN VILLAGE BATANGTORU REGENCY SOUTH TAPANULI - Muhammad Fadli; Fajar Pasaribu; Satria Tirtayasa; Hasrudy Tanjung (Jurnal Ekonomi, 2023)
The purpose of this study was to determine whether there is an effect of competence of field agricultural extension (PPL) on the quality of Human Resources (HR) farmer groups in sumuran village, batangtoru District, South tapanuli Regency. To determine whether there is the influence of the skills of field agricultural extension workers (PPL) on the quality of Human Resources (HR) of farmer groups in sumuran village, batangtoru District, South tapanuli Regency. To determine whether there is the influence of Education owned field agricultural extension (PPL) on the quality of Human Resources (HR) farmer groups in sumuran village, batangtoru District, South tapanuli Regency. To determine whether there is an effect of competence, skills and education of field agricultural extension (PPL) on the quality of Human Resources (HR) farmer groups in sumuran village, batangtoru District, South tapanuli Regency. The method in this study is the approach in this study is to use an associative approach, associative approach is an approach in which to determine that there is a relationship or influence between the two variables. Based on the research conducted shows that the competence, skills and education of each significantly affect the quality of human resources. And competencies, skills and education together significantly influence the quality of human resources.